Global trends in the metallurgical industry and their impact on the Belarusian metallurgy - Goloventchik, Galina G. (Journal of the Belarusian State University. Economics, 2018)
The main trends in the development of the world metallurgy, which are important for the Republic of Belarus, are revealed. The state of the Belarusian metallurgical industry is assessed. The first-priority directions of modernization of the metallurgical complex are examined. Proposals are given for increasing the economic activity of metallurgical enterprises on the basis of innovations and the corresponding state industrial policy.
Keywords: metallurgical industry; innovative economy; modernization; innovations; investments